Transforming Deities: Modern Pagan Projects of Revival and Reinvention. (12th October 2018) - Rountree, Kathryn
Abstract : This article examines a variety of ways in which deities from the ancient Mediterranean have been re-appropriated, re-interpreted, transformed, and invented for contemporary religious and socio-political purposes by local Pagan communities—especially in Greece, Italy, Iberia, and Malta—and by followers of the global Goddess spirituality movement.